2020
DOI: 10.1007/s00394-020-02412-z
|View full text |Cite
|
Sign up to set email alerts
|

Six months vitamin K treatment does not affect systemic arterial calcification or bone mineral density in diabetes mellitus 2

Abstract: Purpose Vitamin K-dependent proteins are involved in (patho)physiological calcification of the vasculature and the bones. Type 2 diabetes mellitus (DM2) is associated with increased arterial calcification and increased fractures. This study investigates the effect of 6 months vitamin K2 supplementation on systemic arterial calcification and bone mineral density (BMD) in DM2 patients with a history of cardiovascular disease (CVD). Methods In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…However, despite the encouraging results mentioned above, no association has been found between VitK2 intake, reduced stroke risk [ 122 ], CVD mortality [ 127 ] and arterial calcification in Type 2 diabetes and CVD patients [ 128 , 129 ].…”
Section: Vitamin K2 and Vascular Healthmentioning
confidence: 99%
“…However, despite the encouraging results mentioned above, no association has been found between VitK2 intake, reduced stroke risk [ 122 ], CVD mortality [ 127 ] and arterial calcification in Type 2 diabetes and CVD patients [ 128 , 129 ].…”
Section: Vitamin K2 and Vascular Healthmentioning
confidence: 99%
“…A post-hoc analysis of this trial was recently published to investigate the effect of vitamin K 2 on CT-based arterial calcification mass, quantified in several large arterial beds, and there was no significant difference between placebo and supplemented groups. 111 Both studies were limited by the short duration of follow-up, small sample size, low percentage of severe vitamin K deficiency and high dropout rates. Despite the evident potential of vitamin K 2 in modulating vascular and valvular calcification, its definitive role is yet to be fully established.…”
Section: Vitamin K-dependent Proteins and Cardiovascular Healthmentioning
confidence: 99%
“…While some studies, especially in female postmenopausal patients after vitamin K1 supplementation showed an unchanged atherosclerotic index in the carotid comm. artery, in some studies these were even decreased [112,113] .…”
Section: Discussionmentioning
confidence: 92%